Foundations of Sustainable Business: Theory, Function, and Strategy - Nada R. Sanders; John D. Wood (Hoboken, NJ Wiley, 2020)
The second edition of Sustainable Business prepares future business leaders to tackle the most crucial social and environmental issues of our time. This engaging textbook provides students with a comprehensive, balanced introduction to integrating sustainable business policies into all core business functions and processes. The text employs a qualitative-based learning process to help students understand how leadership, finance, accounting, risk management, marketing, supply chain management, and operations can be adapted to meet the sustainability goals of the 21st century. Looking at sustainable business from the managerial viewpoint, the fully-updated new edition explains how and why business is evolving due to increased consumer and regulatory pressure for sustainable performance. Business topics are first introduced in the same manner as traditional MBA programs, and then examined through the lens of sustainably. The text incorporates real-life examples of social and environmental leadership to demonstrate the efficacy of good sustainable business decisions, and illustrates the negative ramifications of outdated, purely economic-driven managerial decision-making. Influential concepts based on interdisciplinary research in sustainability are discussed in detail, and practical insights address how to turn policy into practice in the workplace.
Keywords: Business; Sustainability; (BIN3038-N) Contemporary Issues in Business Management